(untitled) (The Strategic Review for Southern Africa, 2025)
This paper interrogates the electoral decline of former liberation movements in Southern Africa and the implications for democratic consolidation. Focusing on South Africa’s African National Congress (ANC), Namibia’s South West Africa People’s Organisation (SWAPO), the Zimbabwe African People’s Union- Patriotic Front (ZANU–PF) and the Front for the Liberation of Mozambique (FRELIMO), it employs a comparative qualitative design to analyse electoral data, party manifestos, parliamentary debates and media reports. Findings reveal three key issues. First, liberation legitimacy as a political resource is steadily eroding, undermined by corruption, socio-economic crises and generational shifts that weaken historical loyalties. Second, trajectories diverge: South Africa and Namibia point to potential democratic renewal through pluralism and coalition governance, while Zimbabwe and Mozambique illustrate how liberation decline can entrench authoritarian resilience through coercion and institutional capture. Third, the implications for democratic consolidation are contingent, rather than uniform. Institutional strength and the coherence of the opposition shape whether electoral realignments generate pluralism or reinforce authoritarianism. The analysis demonstrates that the decline of liberation hegemony is neither linear nor uniformly democratising. Instead, it opens contested political pathways that reveal the conditions under which the decline of the dominant party strengthens or undermines democratic consolidation in post-liberation states.